2012
DOI: 10.1021/jp306636w
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization and Aggregation of the Solar Cell Dye D149

Abstract: D149, a metal-free indoline dye, is one of the most promising sensitizers for dye-sensitized solar cells (DSSCs) and has shown very high solar energy conversion efficiencies of 9%. Effective electron injection from the excited state is a prerequisite for high efficiencies and is lowered by competing deactivation pathways. Previous investigations have shown surprisingly short-lived excited states for this dye, with maximum lifetime components of 100–720 ps in different solvents and less than 120 ps for surface-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
169
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(184 citation statements)
references
References 37 publications
14
169
0
1
Order By: Relevance
“…This is consistent with Horiuchi et al's [14] original paper on D149-sensitized DSCs. In that paper and later papers [18,22], the spectral red shift was claimed to be due to aggregate formation; a theoretical calculation was also reported [23]. In our opinion, the aggregate formation model proposed by these researchers is not supported by direct experimental evidence.…”
Section: Effect Of Aggregationmentioning
confidence: 87%
See 2 more Smart Citations
“…This is consistent with Horiuchi et al's [14] original paper on D149-sensitized DSCs. In that paper and later papers [18,22], the spectral red shift was claimed to be due to aggregate formation; a theoretical calculation was also reported [23]. In our opinion, the aggregate formation model proposed by these researchers is not supported by direct experimental evidence.…”
Section: Effect Of Aggregationmentioning
confidence: 87%
“…A possible interpretation is that the molecular structures in solution and on the semiconductor surface are different. Recently, El-Zohry et al [18] reported that photoisomerization of D149 in solution is suppressed when dyes are adsorbed on semiconductor films. This finding implies that the structure of D149 is restricted on the TiO 2 surface.…”
Section: Effect Of Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rutheniumbased sensitizers such as the N3 dye/ N719 dye [9,10,23] and black dye [24] were rigorously tested as light har-vesters and reached remarkable overall power conversion efficiency (η) in the range of 11% under Air Mass 1.5 (AM 1.5) irradiation while organic photosensitizers have reached power conversion efficiency (PCE) in the range of 5-8% [25][26][27][28][29][30][31]. Metal-free indoline dye (D149) is the most effective photosensitizer for DSSCs and has attained very high efficiencies of 9% [32]. Recently, devices fabricated by using ruthenium (II) complexes with cobalt (3+/2+) based electrolytes have achieved efficiencies of 9.4% [33].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies regarding the electron injection from the excited state of D149 to ZnO [10,[16][17][18][19][20][21] revealed that the electron injection occurs on a femtosecond to picosecond timescale and that electron injection into ZnO surface states is a non-negligible path that slows down electron injection dynamics. [11,22] Transient absorption spectroscopy (TAS) measurements performed by us previously on complete D149/ZnO cells with a variety of electrolytes based on the I À /I 3 À redox couple yielded characteristic times for primary charge injection, parasitic recombination, and regeneration rates.…”
Section: Introductionmentioning
confidence: 99%